Absolute to Obsolete: A Toxic Journey (Journal of Forensic Medicine & Toxicology, 2025)
As scientific knowledge expands and technology advances, certain traditional practices in toxicology have become obso lete in the current era. This article delves into some of these outdated approaches, highlighting the need for their replace ment with more modern and sophisticated methods. The article highlights the importance of toxicology as a discipline,  the current scenario and practice and why we need to bring change in study material taught to undergraduate and post graduate students. The topics which are still taught and are of no relevance in the present time need to be removed and  the common treatment and testing methods which could be useful in clinical practice should be given importance. By  shedding outdated practices, toxicology in the current era aims to provide more accurate, reliable, and applicable insights  into the potential risks posed by various chemicals on human health and the environment.
Keywords: Toxicology; Absolute; Obsolete